Serum concentrations of corticosterone and sex hormones and their relationship in farmed Morelet’s crocodile (Crocodylus moreletii) - Gutiérrez-Cervantes, Adrián; Ahuja-Aguirre, Concepción; López-DeBuen, Lorena; Viveros-Peredo, Sergio; Morales-Mávil, Jorge E; Montiel-Palacios, Felipe (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Crocodile farming aims to produce high-quality skins from captive crocodilians. Captivity usually exposes the animals to stressful conditions, resulting in increased serum corticosterone (CORT) levels that correlate negatively with those of sex hormones and reproductive success. Objective: To evaluate serum concentrations of CORT and sex hormones and their relationship in farmed Morelet’s crocodiles (Crocodylus moreletii) during the non-breeding (NBS) and breeding (BS) seasons. Methods: The study included 59 adult crocodiles (29 females and 30 males). One blood sample was collected in NBS (n=31) and BS (n=28) from each crocodile to determine serum concentrations of CORT, estradiol (E2), progesterone (P4), and testosterone (T). Crocodiles were kept in mixed-sex groups and were fed once or twice a week throughout the study. Results: In females, CORT was higher in NBS (p<0.05) but had no correlation with E2 or P4 in any season (p>0.05). In males, CORT was similar in NBS and BS (p>0.05) and had no correlation with T (p>0.5). Conclusion: The CORT levels had no effect on sex hormones. This could be explained by low CORT levels resulting from farming conditions where the animals were not exposed to severe or chronic stress.